Factors associated with fertility intentions among women living with and without human immunodeficiency virus in Zambia - David Mulemena; Million Phiri; Namuunda Mutombo; Chinyama Lukama; Julius Nyerere Odhiambo; Chester Kalinda (Women's Health, 2023)
Background: Zambia is one of the countries in sub-Saharan Africa with a high prevalence of human immunodeficiency virus among women of reproductive age. Notably, the literature shows that human immunodeficiency virus status is one of the factors that influence fertility intention among women of reproductive age. With increased access, uptake and coverage of anti retroviral therapy, there is a need to understand the influence of human immunodeficiency virus status on fertility intentions of women of reproductive age in Zambia. Objectives: The purpose of this study was to determine the fertility intentions of both mothers living with human immunodeficiency virus and mothers living without human immunodeficiency virus in Zambia. Design: This study adopted a cross-sectional design using data collected by the Zambia Demographic and Health Survey conducted in 2018. The study sample comprised 7983 mothers in the reproductive age (15–49 years), of which 6704 were mothers living without human immunodeficiency virus and 1279 were mothers living with human immunodeficiency virus. Methods: Here, we determined the fertility intentions of mothers living with human immunodeficiency virus and mothers living without human immunodeficiency virus using secondary data. Multivariable logistic regression models were used to determine the association of individual and household socio-demographic factors on fertility intentions of mothers living with human immunodeficiency virus and mothers living without human immunodeficiency virus in Zambia. Results: Fertility intention among mothers living with human immunodeficiency virus was 42.1% while that on mothers living without human immunodeficiency virus was 55.5%. Regardless of human immunodeficiency virus status, fertility intention reduced with increasing age. Mothers aged 35–49 years who were living with human immunodeficiency virus (adjusted odds ratio = 0.12, 95% confidence interval = 0.06–0.24) and mothers aged 35–49 years who were living without human immunodeficiency virus (adjusted odds ratio = 0.18, 95% confidence interval = 0.13–0.26) had lower odds of intention to have another child compared to mothers aged 15–24 years. Furthermore, married mothers living with human immunodeficiency virus and those living without human immunodeficiency virus had increased odds of intention of having another child (adjusted odds ratio = 2.52, 95% confidence interval = 1.36–4.66) and (adjusted odds ratio = 3.21, 95% confidence interval = 2.36–4.36), respectively. Conclusion: The study has established that age, marital status, parity and employment status were associated with fertility intention among women living with and without human immunodeficiency virus. The results necessitate the need for enhanced maternal health education for mothers regardless of human immunodeficiency virus status. Furthermore, there is a need for continuous counselling for both women living with human immunodeficiency virus and without human immunodeficiency virus during their routine human immunodeficiency virus care, to improve and enhance pregnancy outcomes.